Pengaruh Komisaris Independen, Komite Audit, Board Gender Diversity, dan CSR terhadap Tax Aggressiveness pada Perusahaan Kompas100 Sebelum dan Selama Pandemi - Rizki, Aisah Amalia; Rahayu, Dewi Pudji; Larasati, Meita (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of independent commissioner, audit committee, board gender diversity, and CSR on tax aggressiveness The population and sample in this study were KOMPAS100 index companies listed in Indonesian Stock Exchange before and during the Covid-19 pandemic for the 2018-2021 period. The sampling technique of this study was using purposive sampling technique. The number of research samples before the Covid-19 pandemic was 69 samples and during the Covid-19 pandemic was 85 samples. The data analysis technique used in this study is multiple linear regression. Before the Covid-19 pandemic, it was found that independent commissioner, audit committee, board gender diversity, and firm size had no impact on tax aggressiveness, while CSR and leverage had an impact on tax aggressiveness. During the Covid-19 pandemic, it was found that CSR, board gender diversity, leverage, and firm size had no impact on tax aggressiveness, while the independent commissioner and audit committee had an impact on tax aggressiveness.